The Influence Of Training, Work Environment, And Job Satisfaction On Employee Work Productivity At PT. Pelindo Multiterminal - Rizki Ramadhan; Wilchan Robain (Universitas Dehasen Bengkulu, 2026)
This research was conducted at PT. Pelindo Multiterminal, a government-owned company, with the aim of determining the effect of job training, work environment, and job satisfaction on employee productivity. The research population was 43 employees working in the company's HR performance learning division, and the sampling was carried out using saturated sampling, resulting in 43 respondents. The type of data used was primary data, while the data sources were secondary data. Data collection techniques used were literature studies, surveys, and observations. Data analysis techniques used were multiple linear regression, classical assumption tests, and hypothesis tests. The results showed that job training, work environment, and job satisfaction partially and simultaneously had a positive and significant effect on employee productivity. There was a strong correlation between job training, work environment, and job satisfaction with employee productivity, with a percentage of 56.10%, and the remaining 43.9% could be explained by other variables not studied.